Prosecutors’ experiences investigating alleged sexual abuse against pre-schoolers - Ernberg, Emelie (Psychology, crime & law, 2020)
Investigating and prosecuting cases of alleged child sexual abuse is challenging, especially if the report concerns a young child. The present study aimed to examine prosecutors’ experiences investigating and prosecuting cases of alleged sexual abuse of pre-schoolers. Ninety-four Swedish child abuse prosecutors participated in a 2017 national survey regarding their work with these cases and their experiences collaborating with police and Child Protective Services (CPS). Their responses were analysed using both quantitative (descriptive and inferential statistics) and qualitative (thematic analysis) approaches. The prosecutors described difficulties eliciting and evaluating testimony from the youngest children, alongside a lack of corroborative evidence, as the main challenges in investigating cases of alleged sexual abuse of pre-schoolers. Some prosecutors reported that an ongoing CPS investigation could negatively affect the criminal investigation. Furthermore, the quality of the investigative child interview was described as paramount to the investigation and as something that could be affected by the interviewer as well as the resources available to the police. Suggestions for future research and potential practical implications for CSA investigations involving pre-schoolers are discussed.